First Principles Study of Titanium Hydrides, TiHn: n = 1, 2, 3; Energetics and Phase Transition - KANAGAPRABHA, Shunmugam; RAJESWARAPALANICHAMY, Ratnavelu; IYAKUTTI, Kombiah (Walailak Journal of Science and Technology (WJST), 2014)
The electronic structure and structural phase transition of TiHn (n = 1, 2 and 3) are investigated using the Tight-Binding Linear Muffin-Tin Orbital (TB-LMTO) method with Local density approximation (LDA) and Atomic sphere approximation (ASA). The equilibrium geometries, the electronic band structure, and the total and partial Density of States (DOS) are obtained under various pressures, and are analyzed in comparison with the available experimental and theoretical data. It is predicted that the most stable structure of Titanium hydride is a cubic structure at normal pressure. Both TiH and TiH2 undergo a structural phase transition from a cubic to a hexagonal phase under high pressure. The stability of TiM2H and TiMH2 is analyzed. doi:10.14456/WJST.2014.7